ZIF-8 derived iron diatomic nitrogen-doped porous carbon material as well as preparation method and application thereof
By preparing ZIF-8-derived iron diatomic nitrogen-doped porous carbon materials, the problems of high thermal decomposition temperature and low heat release of ammonium perchlorate were solved, and the combustion performance of AP-based solid propellants was regulated. The materials exhibit good catalytic effects and a simple preparation process.
Patent Information
- Application Number
- CN202511474497.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-12-16
AI Technical Summary
Ammonium perchlorate, a common solid propellant, has a high thermal decomposition temperature, low heat release, and is not concentrated, making it difficult to meet the combustion performance requirements of modern national defense. Common catalysts also suffer from problems such as easy agglomeration, complex preparation processes, and high costs.
Using ZIF-8-derived iron diatomic nitrogen-doped porous carbon materials, Fe2-ZIF precursors were prepared using zinc salts and Fe2(CO)9 as raw materials, and Fe2-NCN catalysts were obtained by high-temperature sintering. Iron atoms were loaded or embedded in the nitrogen-doped porous carbon framework in the form of atomic pairs, forming a catalyst with high specific surface area and good dispersion.
It significantly reduces the pyrolysis temperature of ammonium perchlorate, increases the heat release, improves combustion performance, has a simple preparation process that is easy to scale up for production, and is suitable for AP-based solid propellants.
Smart Images

Figure CN121135548A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of solid propellants, in particular to a ZIF-8 derived iron diatomic nitrogen doped porous carbon material and a preparation method and application thereof. BACKGROUND
[0002] Solid propellants are widely used in the power systems of advanced strategic and tactical missile weapons, and improving the performance level of solid propellants plays a key role in improving the overall combat effectiveness of weapon equipment.
[0003] Solid propellants release chemical energy through combustion and then convert it into kinetic energy, and the combustion performance directly affects the trajectory performance of solid rocket engines, and is one of the most important performance indicators of solid propellants. The oxidizer, as the oxygen source for propellant combustion, accounts for a high proportion in the propellant formula, and its thermal decomposition process has an important influence on the combustion behavior and energy release of the propellant; generally speaking, the lower the thermal decomposition temperature of the energetic component, the higher the burning rate, and vice versa; therefore, the trend of the thermal decomposition temperature of the energetic material before and after adding a catalyst can also predict the increase / decrease and change range of the burning rate of the propellant after adding the catalyst. Ammonium perchlorate (AP) is one of the most widely used oxidizers in solid propellants so far due to its high effective oxygen content, large density, large gas generation amount and low price. However, the thermal decomposition process of AP has problems such as high thermal decomposition temperature, low heat release amount and non-concentrated heat release, which is an important factor restricting the development of AP-based solid propellants. In order to meet the performance requirements of solid propellants for modern national defense construction and effectively regulate the combustion performance, it is necessary to improve the thermal decomposition performance of AP.
[0004] Adding a combustion catalyst is one of the most effective ways to improve the thermal decomposition performance of AP, and common combustion catalysts include metal elements, metal oxides, metal composite oxides and carbon-based composite catalysts, but they usually have problems such as easy oxidation and reduction of catalytic activity, complex preparation process and high cost, which are difficult to meet the actual needs of engineering applications. SUMMARY
[0005] The application aims to overcome the above-mentioned deficiencies in the prior art, and provides a ZIF-8 derived iron diatomic nitrogen doped porous carbon material and a preparation method and application thereof.
[0006] The application solves the technical problems by using the following technical solutions.
[0007] The application provides a ZIF-8 derived iron bimolecular nitrogen doped porous carbon material, and the composition of the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material is Fe2-NCN, wherein: Fe atoms are loaded on the surface of a nitrogen doped porous carbon framework or embedded in the nitrogen doped porous carbon framework in the form of an atomic pair, and the particle size of a single particle is between 400 and 500 nm.
[0008] The application provides a preparation method of the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material, which comprises the following steps: taking a zinc salt and Fe2(CO)9 as raw materials, and obtaining a precursor Fe2-ZIF through reaction; and obtaining the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material Fe2-NCN through high-temperature sintering of the precursor Fe2-ZIF.
[0009] The application provides an application of the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material in a propellant.
[0010] The application has the following beneficial effects: Compared with an AP pyrolysis (combustion) catalyst Fe2O3 commonly used in an existing solid propellant system and a catalyst such as carboxin, the ZIF-8 derived iron bimolecular nitrogen doped porous carbon catalyst obtained by the application has a better AP pyrolysis catalytic effect, and specifically, the pyrolysis temperature of a mixture after blending with AP is lower, and the apparent heat release is more; and the preparation process of the application is simple, the reaction conditions are mild, and the production is easy to scale up.
[0011] The ZIF-8 derived iron bimolecular nitrogen doped porous carbon catalyst obtained by the application has a significant AP pyrolysis catalytic effect, and the introduction of the catalyst can greatly reduce the pyrolysis peak temperature of AP and significantly improve the heat release, which is helpful to realize the combustion performance regulation of an AP-based solid propellant, and is expected to be applied as a new type of combustion catalyst in the AP-based solid propellant. BRIEF DESCRIPTION OF DRAWINGS
[0012] In order to more clearly illustrate the technical solutions of the embodiments of the application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the application, and therefore should not be regarded as a limitation on the scope, and for those skilled in the art, other related drawings can also be obtained without creative labor on the basis of these drawings.
[0013] Figure 1 For pure AP and AP-Fe2-NCN mixed powder under the same ignition condition DZ-1 (10wt%) laser ignition high-speed photography comparison chart; Figure 2 For Fe2-NCN DZ-1 SEM diagram (a diagram and c diagram) of catalyst precursor and catalyst sample and Fe2-NCN1100 SEM images of the catalyst precursor and catalyst sample (Figures b and d); Figure 3 Fe2-NCN DZ-1 AC-STEM and Fe element Mapping images of the catalyst sample; Figure 4 XRD images of Fe2-NCN catalysts prepared at different sintering temperatures (900℃, 1000℃, 1100℃); Figure 5 Figure (a) is the N2 adsorption-desorption curve of the catalyst and its precursor, and Figure (b) is the pore size distribution curve of the catalyst and its precursor; Figure 6 Figure is the effect of Fe2-NCN catalyst (sintering temperature 1000℃, sintering time 3h) samples prepared at different dosages of di-nonyl iron carbonyl [Fe2(CO)9] on the catalytic effect of AP pyrolysis; Figure 7 Figure is the effect of Fe2-NCN catalyst (same dosage, sintering time 3h) samples prepared at different sintering temperatures (900℃, 1000℃, 1100℃) on the catalytic effect of AP pyrolysis; Figure 8 Figure is the effect of Fe2-NCN catalyst (same dosage, sintering temperature 1000℃) samples prepared at different sintering times (2h, 3h, 4h) on the catalytic effect of AP pyrolysis; Figure 9 Figure is the thermal analysis (DSC) curve of pure AP and AP-Fe2-NCN DZ-1 (10wt%) mixed powder at different heating rates; Figure 10 Figure is the fitted 1000 / T DZ-1 -ln(β / T p p 2 relationship curve of pure AP and AP-Fe2-NCN DETAILED DESCRIPTION
[0014] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. If specific conditions are not specified in the embodiments, conventional conditions or manufacturer recommended conditions are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.
[0015] A ZIF-8 derived iron diatomic nitrogen doped porous carbon material, a preparation method and application thereof will be described in detail below.
[0016] In a first aspect, the embodiment of the present application provides a ZIF-8 derived iron bimolecular nitrogen doped porous carbon material, the composition of the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material is Fe2-NCN, wherein: the Fe atoms are loaded on the surface of the nitrogen doped porous carbon framework or embedded in the nitrogen doped porous carbon framework in the form of atom pairs, and the particle size of a single particle is between 400-500 nm.
[0017] The embodiment of the present application provides a ZIF-8 derived iron bimolecular nitrogen doped porous carbon material, the composition of the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material is Fe2-NCN, that is, the iron bimolecular and the nitrogen monatomic are doped in the porous carbon material at the same time, and the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material can significantly reduce the ignition threshold of AP and obviously improve the ignition performance as a catalyst.
[0018] In a second aspect, the embodiment of the present application provides a preparation method of a ZIF-8 derived iron bimolecular nitrogen doped porous carbon material, which comprises the following steps: taking a zinc salt and Fe2(CO)9 as raw materials, and obtaining a precursor Fe2-ZIF through reaction; and obtaining the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material Fe2-NCN through high-temperature sintering of the precursor Fe2-ZIF.
[0019] ZIFs have the advantages of high specific surface area, self-doped nitrogen, open pore structure, universal topology and milder synthesis conditions, and are widely used in multiple fields. As a very representative ZIF, ZIF-8 is a three-dimensional spatial nanocage with a rhombohedral dodecahedron structure assembled by zinc ions and dimethyl imidazole ligands.
[0020] In order to solve the problems of high pyrolysis temperature, low heat release and non-concentrated heat release in the thermal decomposition process of AP in propellants, the present application provides a ZIF-8 derived iron bimolecular nitrogen doped porous carbon material, and a preparation method thereof, which comprises the following steps: taking a zinc salt and Fe2(CO)9 as raw materials, and obtaining a precursor Fe2-ZIF through reaction; and obtaining the ZIF-8 derived iron bimolecular nitrogen doped porous carbon material Fe2-NCN through high-temperature sintering of the precursor Fe2-ZIF. In the above preparation process, the iron bimolecular in the raw materials is partially doped into the ZIF-8 framework during the formation of the precursor, and under the condition of high-temperature sintering, the zinc in the metal framework ZIF-8 volatilizes, and the iron bimolecular in the raw material Fe2(CO)9 partially replaces the positions of part of the zinc atoms, so as to be loaded on the surface of the porous carbon material. Whether it is doped or loaded, the coordination is mainly N coordination.
[0021] It is worth mentioning that the pore-forming effect of Zn volatilization in the sintering process realizes the formation of more cavities, realizing high specific surface area; the confinement effect makes the metal disperse efficiently and reduces the aggregation, better playing the catalytic activity. The experimental results show that the ZIF-8 derived iron diatomic nitrogen doped porous carbon material obtained has excellent AP pyrolysis catalytic performance, can reduce the apparent activation energy of AP, and makes the two-stage decomposition process of AP at high and low temperatures into one-stage concentrated pyrolysis, the high and low temperature decomposition peaks are combined at one place and the pyrolysis temperature is greatly lowered to about 307 DEG C, which has high application value as a propellant and gun propellant combustion catalyst.
[0022] In some alternative embodiments, the method comprises the following steps: dispersing Zn(NO3)2.6H2O and Fe2(CO)9 in an organic solvent, uniformly ultrasonic dispersing to obtain an A solution; dispersing a certain amount of 2-methylimidazole in an organic solvent, uniformly ultrasonic dispersing to obtain a B solution; rapidly transferring the A solution to the B solution and stirring, then centrifugally separating and washing the solid product, and then drying to obtain a catalyst precursor Fe2-ZIF; sintering the catalyst precursor Fe2-ZIF under an inert atmosphere to obtain a ZIF-8 derived iron diatomic nitrogen doped porous carbon material Fe2-NCN.
[0023] In some alternative embodiments, the organic solvent comprises one or more of anhydrous methanol and N,N-dimethylformamide.
[0024] In some alternative embodiments, the mass ratio of Fe2(CO)9 to Zn(NO3)2.6H2O is 0.023-0.048:1.
[0025] In some alternative embodiments, the A solution is rapidly transferred to the B solution and stirred, the stirring process does not need heating, the stirring rate is controlled to be 400-600 r / min, and the time is 8-12 h.
[0026] In some alternative embodiments, in the high-temperature sintering process, the temperature programming rate is controlled to be 5 DEG C / min, the sintering temperature is controlled to be 900-1100 DEG C, and the holding time is controlled to be 120-240 min.
[0027] In some alternative embodiments, the inert atmosphere comprises one of nitrogen and argon, preferably the inert atmosphere is introduced for not less than 30 min in advance, and the high-temperature sintering is performed after air is sufficiently exhausted.
[0028] In a third aspect, an embodiment of the present application provides a use of the above-mentioned ZIF-8 derived iron diatomic nitrogen doped porous carbon in propellants.
[0029] In some alternative embodiments, the ZIF-8 derived Fe-biatomic N-doped porous carbon as catalyst is applied in the thermal decomposition of AP, AP-based solid propellant, and combustion of explosives.
[0030] The application will be further described below with reference to the examples.
[0031] Example 1 A preparation method of a ZIF-8 derived Fe-biatomic N-doped porous carbon catalyst comprises the following steps: 8.4g of Zn(NO3)2·6H2O and 0.2g of Fe2(CO)9 were dissolved in 200mL of anhydrous methanol to form a solution A; 13.2g of 2-methylimidazole was dissolved in 100mL of anhydrous methanol to form a solution B; the solutions were uniformly dispersed in an ultrasonic cleaner for 10min. The solution A was transferred into the solution B, and stirred at a speed of 400r / min at room temperature overnight. The product was collected by centrifugal washing with anhydrous methanol and ethanol alternately, and then transferred into a vacuum drying oven for drying overnight. The catalyst precursor Fe2-ZIF was obtained by grinding and collecting. The precursor was placed in an alumina crucible and transferred into a tube furnace, and N2 was introduced for 30min to exhaust air. The temperature was raised to 1000℃ at a rate of 5℃ / min and kept for 3h. The product was collected after natural cooling to room temperature, and a catalyst sample was obtained, which was named as Fe2-NCN.
[0032] Example 2 A preparation method of a ZIF-8 derived Fe-biatomic N-doped porous carbon catalyst comprises the following steps: 8.4g of Zn(NO3)2·6H2O and 0.2g of Fe2(CO)9 were dissolved in 200mL of anhydrous methanol to form a solution A; 13.2g of 2-methylimidazole was dissolved in 100mL of anhydrous methanol to form a solution B; the solutions were uniformly dispersed in an ultrasonic cleaner for 10min. The solution A was transferred into the solution B, and stirred at a speed of 400r / min at room temperature overnight. The product was collected by centrifugal washing with anhydrous methanol and ethanol alternately, and then transferred into a vacuum drying oven for drying overnight. The catalyst precursor Fe2-ZIF was obtained by grinding and collecting. The precursor was placed in an alumina crucible and transferred into a tube furnace, and N2 was introduced for 30min to exhaust air. The temperature was raised to 1000℃ at a rate of 5℃ / min and kept for 3h. The product was collected after natural cooling to room temperature, and a catalyst sample was obtained, which was named as Fe2-NCN. DZ-1 . The precursor was placed in an alumina crucible and transferred into a tube furnace, and N2 was introduced for 30min to exhaust air. The temperature was raised to 1000℃ at a rate of 5℃ / min and kept for 3h. The product was collected after natural cooling to room temperature, and a catalyst sample was obtained, which was named as Fe2-NCN DZ-1 .
[0033] Example 3 A preparation method of a ZIF-8 derived iron diatomic nitrogen doped porous carbon catalyst, comprising the following steps: 8.4g of Zn(NO3)2·6H2O and 0.4g of Fe2(CO)9 were weighed and dissolved in 200mL of N-N dimethylformamide solvent to obtain solution A; 13.2g of 2-methylimidazole was weighed and dissolved in 100mL of N-N dimethylformamide solvent to obtain solution B; the solutions were uniformly dispersed in an ultrasonic cleaner for 10min. The solution A was transferred to the solution B, and stirred at a speed of 500r / min at room temperature overnight. The product was collected by centrifugal washing with anhydrous methanol and ethanol as the washing agent alternately, and then transferred to a vacuum drying oven for drying overnight. The catalyst precursor Fe2-ZIF was obtained by grinding and collecting. DZ-2 The precursor was ground and placed in an alumina crucible and transferred to a tube furnace. N2 atmosphere was introduced for 30min to exhaust air, and then the temperature was raised to 1000℃ at a rate of 5℃ / min and kept for 3h. The product was collected after natural cooling to room temperature to obtain the catalyst sample, which was named Fe2-NCN DZ-2 .
[0034] Example 4 A preparation method of a ZIF-8 derived iron diatomic nitrogen doped porous carbon catalyst, comprising the following steps: 8.4g of Zn(NO3)2·6H2O and 0.4g of Fe2(CO)9 were weighed and dissolved in 200mL of N-N dimethylformamide solvent to obtain solution A; 13.2g of 2-methylimidazole was weighed and dissolved in 100mL of N-N dimethylformamide solvent to obtain solution B; the solutions were uniformly dispersed in an ultrasonic cleaner for 10min. The solution A was transferred to the solution B, and stirred at a speed of 500r / min at room temperature overnight. The product was collected by centrifugal washing with anhydrous methanol and ethanol as the washing agent alternately, and then transferred to a vacuum drying oven for drying overnight. The catalyst precursor Fe2-ZIF was obtained by grinding and collecting. DZ-1 The precursor was ground and placed in an alumina crucible and transferred to a tube furnace. N2 atmosphere was introduced for 30min to exhaust air, and then the temperature was raised to 1000℃ at a rate of 5℃ / min and kept for 3h. The product was collected after natural cooling to room temperature to obtain the catalyst sample, which was named Fe2-NCN 900 .
[0035] Example 5 A preparation method of a ZIF-8 derived iron diatomic nitrogen doped porous carbon catalyst, comprising the following steps: Take 8.4 g Zn(NO3)2·6H2O, 0.3 g Fe2(CO)9, and dissolve them in 200 mL of anhydrous methanol, and mark it as solution A; take 13.2 g 2-methylimidazole and dissolve it in 100 mL of anhydrous methanol solvent, and mark it as solution B; place them in an ultrasonic cleaner and ultrasonically disperse for 10 min until the solution is uniformly dispersed. Transfer solution A to solution B, and stir at a speed of 600 r / min at room temperature overnight. After washing and centrifuging with anhydrous methanol and ethanol as the washing agent, collect the product and transfer it to a vacuum drying oven to dry overnight, and grind to obtain the catalyst precursor Fe2-ZIF DZ-1 . After grinding, place the precursor in an alumina crucible and transfer it to a tube furnace, introduce N2atmosphere for 30 min to exhaust air, then increase the temperature from room temperature to 1100℃ at a rate of 5℃ / min and keep it for 3 h, and then collect the product after natural cooling to room temperature to obtain the catalyst sample, which is named Fe2-NCN 1100 .
[0036] Example 6 A method for preparing a ZIF-8 derived iron double-atom nitrogen doped porous carbon catalyst, comprising the following steps: Take 8.4 g Zn(NO3)2·6H2O, 0.3 g Fe2(CO)9, and dissolve them in 200 mL of anhydrous methanol-N-N dimethylformamide solvent (volume ratio 1:1), and mark it as solution A; take 13.2 g 2-methylimidazole and dissolve it in 100 mL of anhydrous methanol-N-N dimethylformamide solvent (volume ratio 1:1) solvent, and mark it as solution B; place them in an ultrasonic cleaner and ultrasonically disperse for 10 min until the solution is uniformly dispersed. Transfer solution A to solution B, and stir at a speed of 600 r / min at room temperature overnight. After washing and centrifuging with anhydrous methanol and ethanol as the washing agent, collect the product and transfer it to a vacuum drying oven to dry overnight, and grind to obtain the catalyst precursor Fe2-ZIF DZ-1 . After grinding, place the precursor in an alumina crucible and transfer it to a tube furnace, introduce N2atmosphere for 30 min to exhaust air, then increase the temperature from room temperature to 1100℃ at a rate of 5℃ / min and keep it for 3 h, and then collect the product after natural cooling to room temperature to obtain the catalyst sample, which is named Fe2-NCN 1000-2 .
[0037] Example 7 A method for preparing a ZIF-8 derived iron double-atom nitrogen doped porous carbon catalyst, comprising the following steps: Take 8.4 g Zn(NO3)2·6H2O, 0.3 g Fe2(CO)9, and dissolve them in 200 mL of anhydrous methanol to obtain solution A; take 13.2 g 2-methylimidazole and dissolve them in 100 mL of anhydrous methanol to obtain solution B; and then ultrasonic dispersion is performed for 10 min in an ultrasonic cleaner until the solution is uniformly dispersed. The solution A is transferred to the solution B, and stirring is performed at a speed of 600 r / min at room temperature overnight. After being washed by anhydrous methanol and ethanol alternately, the product is collected and transferred to a vacuum drying oven for drying overnight, and then the catalyst precursor Fe2-ZIF is obtained by grinding DZ-1 . After being ground, the precursor is placed in an alumina crucible and transferred to a tube furnace, N2atmosphere is introduced for 30 min to exhaust air, and then the temperature is increased to 1000℃ at a rate of 5℃ / min and kept for 4 h. After being naturally cooled to room temperature, the product is collected to obtain the catalyst sample, which is named as Fe2-NCN 1000-4 .
[0038] Test results Figure 1 The AP-catalyst mixed powder laser ignition high-speed photography comparison chart under the same ignition condition can be seen that the AP powder is almost not ignited, while the powder mixed with the catalyst Fe2-NCN DZ-1 is burned violently, which to a large extent shows that the catalyst can reduce the ignition threshold of AP, and has the effect of promoting the combustion and improving the ignition performance of AP. DZ-1
[0039] Figure 2 The (a) and (c) graphs in FIG. 1 are SEM images of the Fe2-NCN DZ-1 catalyst precursor and the catalyst sample, and it can be seen that after being sintered at a high temperature of 1000℃ in an inert atmosphere, the particle surface of the catalyst is obviously slightly rougher than that of the precursor, but the rhombohedron dodecahedron structure can still be basically maintained, and the particle size of a single particle is about 400-500 nm. Figure 2 The (b) and (d) graphs in FIG. 1 are SEM images of the Fe2-NCN 900 catalyst precursor and the catalyst sample, and it can be seen that after being sintered at a high temperature of 900℃ in an inert atmosphere, the particle surface of the catalyst is obviously rougher than that of the precursor, but the rhombohedron dodecahedron structure can still be basically maintained, and the particle size of a single particle is about 400-500 nm.
[0040] Figure 3 The AC-STEM image of the Fe2-NCN DZ-1 catalyst sample can clearly observe the uniformly distributed white bright spots under the high-angle annular dark field (HAADF) mode, and the atomic size is about 0.1 nm, which corresponds to the Fe2-NCNDZ-1 The atomic dispersion of iron atoms in the catalyst, which indicates that the Fe element on the surface of the catalyst is indeed arranged at the atomic dispersion level; most of the iron atoms exist in the form of being adjacent to each other, which is particularly evident in the upper left corner of the Mapping image and the distance between two iron atoms is usually not more than 0.3 nm, which is close to the Fe-Fe atomic spacing, indicating that the iron atoms on the surface of the catalyst should be distributed in the form of iron double atoms.
[0041] Figure 4 The XRD patterns of Fe2-NCN catalysts prepared at different sintering temperatures (900°C, 1000°C, 1100°C) can be seen that the diffraction peaks in the XRD spectrum of the prepared catalysts can almost correspond to C (PDF # 26-1076), and there is no diffraction peak of iron-related species, which further indicates that the Fe element on the surface of the catalyst is most likely dispersed at the atomic scale, which is consistent with the conclusion drawn from the AC-STEM image.
[0042] Figure 5 The (a) graph in FIG. 1 is the Fe2-NCN 1000 The N2 adsorption-desorption curve of the catalyst and its precursor can be seen that the Fe2-ZIF presents a typical I-type adsorption isotherm characteristic, which indicates that there are a large number of microporous structures inside the material, which is consistent with the pore size distribution result of (b) in FIG. 5; the catalyst sample Fe2-NCN 1000 exhibits a typical IV-type isotherm characteristic with a H3-type hysteresis loop, and the appearance of a long and wide hysteresis loop at a high pressure means that there are many disordered mesopores inside the material. From Figure 5 (b) in FIG. 1 can be seen that the pore size distribution of the precursor Fe2-ZIF presents a relatively wide range of 0-107 nm, but mostly concentrates in the range of 1-15 nm, while the pore size distribution of the catalyst Fe2-NCN 1000 is between 2-100 nm, and the same steady decrease in pore volume indicates that the material contains a hierarchical porous structure. Tests show that the specific surface area of the catalyst and its precursor can reach 878.4461 m 2 / g and 1.138.2001 m 2 / g, respectively. A higher specific surface area is also beneficial to providing more catalytically active sites and enhancing its catalytic activity.
[0043] The catalyst Fe2-NCN, Fe2-NCND Z-1 , Fe2-NCN DZ-2 and AP are mixed in a mass ratio of 1:9, and a simultaneous thermal analysis (TG-DSC) test is performed, and the results are as follows Figure 6As shown, Fe2-NCN and Fe2-NCND can be observed. Z-1 Fe2-NCN DZ-2 The introduction of [a specific technology] significantly alters the reaction process of AP thermal decomposition, transforming the original two-stage decomposition process of high and low temperatures into a single-stage concentrated thermal decomposition. The high and low temperature decomposition peaks are merged into one, and are significantly advanced to 316.9°C, 307.9°C, and 313.6°C, respectively.
[0044] The catalyst Fe2-NCN 900 The mixture was thoroughly mixed with AP at a mass ratio of 1:9, and simultaneous thermal analysis (TG-DSC) was performed. The results are as follows: Figure 7 As shown, Fe2-NCN can be seen 900 The introduction of [a specific ingredient] transforms the decomposition peak of AP into a broad peak with a shoulder, with decomposition peak temperatures corresponding to 319.4℃, 334.2℃, and 343.5℃, respectively. From the thermogravimetric curves, it can be seen that when the temperature is between 320℃ and 350℃, AP-Fe2-NCN [a specific ingredient]... 900 The mixed powder exhibited abrupt changes in thermal decomposition rate, which is consistent with the DSC curve. Comprehensive analysis suggests that AP-Fe2-NCN... 900 The thermal decomposition process of the mixed powder was significantly accelerated by nearly 90°C compared to that of the individual AP powder. Similarly, the prepared catalyst Fe2-NCN 1100 The mixture was thoroughly mixed with AP at a mass ratio of 1:9, and simultaneous thermal analysis (TG-DSC) was performed. The results are as follows: Figure 7 As shown, Fe2-NCN can be seen 1100 The introduction of this technology significantly alters the reaction process of AP thermal decomposition, transforming the original two-stage decomposition process of high and low temperatures into a single-stage concentrated thermal decomposition. The high and low temperature decomposition peaks are merged into one point and the decomposition temperature is significantly advanced to 313.9℃.
[0045] The catalyst Fe2-NCN 1000-2 Fe2-NCN 1000-4 The mixture was thoroughly mixed with AP at a mass ratio of 1:9, and simultaneous thermal analysis (TG-DSC) was performed. The results are as follows: Figure 8 As shown, Fe2-NCN can be seen 1000-2 Fe2-NCN 1000-4 The introduction of [a specific technology] significantly alters the reaction process of AP thermal decomposition, transforming the original two-stage decomposition process of high and low temperatures into a single-stage concentrated thermal decomposition. The high and low temperature decomposition peaks are merged into one, and are significantly advanced to 316.9°C and 322.3°C, respectively.
[0046] AP – Fe2-NCN at different heating rates DZ-1 Thermal analysis (DSC) curves of the mixed powder and AP are shown below.Figure 9 It can be seen that with the increase of heating rate, the decomposition peak temperature presents a trend of moving to high temperature direction as a whole; the 1000 / T p and ln(β / T p 2 ) relationship curve is shown in Figure 2, and the fitting curve formula is brought into inverse calculation to obtain the related reaction kinetics parameters as shown in Table 1: Figure 10 Table 1
[0047] It can be seen that the apparent activation energy of the pyrolysis process of the AP-Fe2+NCN DZ-1 mixed powder is greatly reduced from 180.08 kJ / mol of pure AP to 129.62 kJ / mol, and the reduction is 28.08%, which can correspond to the pyrolysis process of the mixed powder being greatly advanced and the combustion process being significantly enhanced after adding the catalyst.
[0048] The above is only the preferred embodiment of the present application and is not used to limit the present application, and the present application can have various modifications and changes for the person skilled in the art. Any modification, equivalent replacement, improvement, etc. within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A ZIF-8 derived iron diatomic nitrogen-doped porous carbon material, characterized in that, The ZIF-8 derived iron diatomic nitrogen-doped porous carbon material is composed of Fe2-NCN, wherein Fe atoms are loaded on the surface of the nitrogen-doped porous carbon framework or embedded in the nitrogen-doped porous carbon framework in the form of atomic pairs, and the particle size of a single particle is between 400 and 500 nm.
2. A method for preparing ZIF-8 derived iron diatomic nitrogen-doped porous carbon material according to claim 1, characterized in that, It includes: using zinc salt and Fe2(CO)9 as raw materials, a precursor Fe2-ZIF is obtained through reaction; the precursor Fe2-ZIF is sintered at high temperature to obtain ZIF-8 derived iron diatomic nitrogen-doped porous carbon material Fe2-NCN.
3. The preparation method according to claim 2, characterized in that, Includes the following steps: Zn(NO3)2·6H2O and Fe2(CO)9 were dispersed in an organic solvent and ultrasonically dispersed to obtain solution A; a certain amount of 2-methylimidazole was dispersed in an organic solvent and ultrasonically dispersed to obtain solution B. Solution A was rapidly transferred to solution B and stirred. The solid product was then separated by centrifugation and washed, and then dried to obtain the catalyst precursor Fe2-ZIF. The catalyst precursor Fe2-ZIF was sintered at high temperature under an inert atmosphere to derive the iron diatomic nitrogen-doped porous carbon material Fe2-NCN from ZIF-8.
4. The preparation method according to claim 3, characterized in that, The organic solvent includes one or more of anhydrous methanol and N,N-dimethylformamide.
5. The preparation method according to claim 3, characterized in that, The mass ratio of Fe2(CO)9 to Zn(NO3)2·6H2O is 0.023~0.048:
1.
6. The preparation method according to claim 3, characterized in that, Transfer solution A to solution B quickly and stir. No heating is required during stirring. Control the stirring rate at 400 r / min to 600 r / min for 8 to 12 hours.
7. The preparation method according to claim 3, characterized in that, During the high-temperature sintering process, the programmed heating rate is controlled at 5℃ / min, the sintering temperature is controlled at 900℃~1100℃, and the holding time is controlled at 120~240min.
8. The preparation method according to claim 3, characterized in that, The inert atmosphere includes either nitrogen or argon. Preferably, the inert atmosphere is introduced for at least 30 minutes before high-temperature sintering, after which the air is fully exhausted.
9. The use of ZIF-8 derived iron diatomic nitrogen-doped porous carbon as described in claim 1 or ZIF-8 derived iron diatomic nitrogen-doped porous carbon prepared by any one of claims 2-8 in propellants.
10. The application according to claim 9, characterized in that, The ZIF-8-derived iron diatomic nitrogen-doped porous carbon is used as a catalyst in the thermal decomposition of AP, AP-based solid propellants, and combustion catalysis of explosives.